Atlantic Water advection versus sea‐ice advances in the eastern Fram Strait during the last 9 ka: Multiproxy evidence for a two‐phase Holocene. (31st May 2013) - Werner, Kirstin; Spielhagen, Robert F.; Bauch, Dorothea; Hass, H. Christian; Kandiano, Evgeniya
<x xml:space="preserve">Abstract</x> [1] A sediment core from the West Spitsbergen continental margin was studied to reconstruct climate and paleoceanographic variability during the last ~9 ka in the eastern Fram Strait (FS). Our multiproxy evidence suggests that the establishment of the modern oceanographic configuration in the eastern FS occurred stepwise, in response to the postglacial sea‐level rise and the related onset of modern sea‐ice production on the shallow Siberian shelves. The late Early and Mid‐Holocene interval (9 to 5 ka) was generally characterized by relatively unstable conditions. High abundance of the subpolar planktic foraminifer species Turborotalita quinqueloba implies strong intensity of Atlantic Water (AW) inflow with high productivity and/or high AW temperatures, resulting in a strong heat flux to the Arctic. A series of short‐lived cooling events (8.2, 6.9, and 6.1 ka) occurred superimposed on the warm late Early to Mid‐Holocene conditions. Our proxy data imply that simultaneous to the complete postglacial flooding of Arctic shallow shelves and the initiation of modern sea‐ice production, strong advance of polar waters initiated modern oceanographic conditions in the eastern FS at ~5.2 ka. The Late Holocene was marked by the dominance of the polar planktic foraminifer species Neogloboquadrina pachyderma, a significant expansion of sea ice/icebergs, and strong stratification of the water column. Although planktic foraminiferal assemblages as well as sea subsurface temperatures suggest a return of slightly strengthened advection of subsurface AW after 3 ka, a relatively stable cold‐water layer prevailed at the sea surface, and the study site was probably located within the seasonally fluctuating marginal ice zone during the Neoglacial period.